Influence of new thermoplastic sizing agents on the mechanical behavior of poly(ether ketone ketone)/carbon fiber composites. Issue 38 (12th June 2015) - Giraud, Isabelle; Franceschi, Sophie; Perez, Emile; Lacabanne, Colette; Dantras, Eric
ABSTRACT In this study, unidirectional poly(ether ether ketone)/carbon fiber (CF) composite sheets were elaborated with unsized, epoxy‐sized, and thermoplastic‐sized CFs by hot‐press molding. The thermoplastic sizings that we used were poly(ether imide) (PEI) and poly(ether ketone ketone) oligomer aqueous dispersions. Scanning electron microscopy observation of the composites freeze fractures showed that unlike unsized or epoxy‐sized CFs, the thermoplastic sizings improved the interaction between the fibers and the matrix. A comparative study of the mechanical relaxations by dynamic mechanical analysis was carried out on the different composites before and after immersion in kerosene. At low temperature, the PEI sizing had a significant influence on the β relaxation, particularly after kerosene immersion. The thermoplastic sizings did not modify the glass‐transition temperature but improved the kerosene resistance on the composites. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42550.